PENERAPAN PRINSIP GOOD ENVIRONMENTAL GOVERNANCE OLEH PEMERINTAH DAERAH KABUPATEN SINTANG DALAM PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Redin - (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2019)
The purpose of this research is to study the application of the principles of good environmental governance by the Sintang District government in environmental protection and management. This research is a normative research. Data collection tools consist of document studies and library studies. The document study was carried out by examining the Sintang District Regulations on protection and the environment. The focus of this research is the application of seven principles of good environmental management according to Belbase, namely: Rule of law; Participation and Representation; Access to information; Transparency and accountability; Decentralization; Institutions and institutions; and access to justice. Data analysis was performed with qualitative analysis and described in a descriptive analytical form. The results of the study show that: 1) Legal regulations consisting of two Regional Regulations and one Sintang Regent Regulation have provided legal certainty for the Sintang Regency regional government in good environmental management, highly determined and designed by the government related to the environmental sector (environment which good) government); 2) Participation and Representation in Environmental Protection and Management that are carried out properly based on community interests; 3) Access to information through the principle of providing information to the public that is transparent and complete is given to before the EIA activities are carried out; 4) Transparency and accountability by providing information for communities and communities to access information about development planning and implementation; 5) Decentralization of government affairs in the field of Environment; 6) Institutions and implementing institutions for regional autonomy in the field of Environment are the Sintang District Environmental Agency; and 7) Access to justice, that is, all Sintang District people without exception can feel the same justice in the use of the environment. Undeniably at this time. These seven principles have been applied by the Sintang District Government in accordance with what is mandated in Law Number 32 of 2009 concerning Environmental Protection and Management. However, at the implementation level there is still a lot to be done which is the principle of good environmental management that has not been able to run optimally regulated in regional regulations and regent regulations. Keywords: Principles of good environmental governance, environmental protection and management.